Philosophy in Britain today - Shanker, Stuart (Croom Helm, 1986)
The diversity of contemporary British philosophical outlooks is revealed in this collection - includes contributions by Karl Popper, R. M. Hare, Ernest Gellner, Gordon Baker, Crispin Wright, Renford Bamborough and others.